Pengaruh Religiusitas dan Kecemasan terhadap Self-Compassion pada Dewasa Awal - Esi Nailulzahwaidar; Bagus Takwin (Fakultas Psikologi Universitas Pancasila, 2022)
Based on previous research it is known that religiosity has a positive correlation with self-compassion and anxiety has a negative correlation with self-compassion. The aims of this study was to see the effect of religiosity and anxiety on self-compassion. This study was done in the quantitative approach with convenience sampling. Participants in this study were 91 people aged 21-40 years. The data was collected using Self-compassion Scale, Religiousity Scale, and State-Trait Anxiety Inventory. Data analysis with SPSS/R program with multiple linear regression tests. Based on the results of the study concluded that there is an effect of religiosity on self-compassion, anxiety on self-compassion, and simultaneously there is an effect of religiosity and anxiety on self-compassion by 58.1%.